PL612 LOFAR station sensitivity measurements in the context of its application for pulsar observations. Issue 7 (1st October 2018) - Błaszkiewicz, L.P.; Lewandowski, W.; Krankowski, A.; Kijak, J.; Froń, A.; Sidorowicz, T.; Dąbrowski, B.; Kotulak, K.; Hajduk, M.
Abstract: The Low Frequency Array (LOFAR) is relatively new interferometric radio telescope. LOFAR operates in poorly explored part of the spectrum (10–240 MHz). In this frequency range pulsars are bright, and LOFAR observations of pulsars are import for probing fundamental physics and the interstellar medium. In this work we present the description of the international LOFAR station frontend and backend parameters related to pulsar observations with a single LOFAR station, based on observations with the Polish station, located in Bałdy near Olsztyn. We present new results from observations aimed at better characterizing the telescope sensitivity. These measurements are important for efficient planning of pulsar observating campaigns. Observations show good sensitivity for pulsar measurements above 25° elevation and show the noise level rises significantly for elevations below 25°.